PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 011 DESA TALANG GEDABU KECAMATAN RAKIT KULIM - ', Yusnirah; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve student learning outcomes IPS class fourth SDN 011 Desa Talang Gedabu Kecamatan Rakit Kulim by applying cooperative learning model type STAD. The subjects were students of class IV of 20 people, consisting of 9 male students and 11 female students. This type of research is the Classroom Action Research (PTK). Based on the results of this study concluded that the results of social studies students before implementation of cooperative learning model STAD is 61, there are seven people were completely and 13 students have not finished with a percentage of 35% completeness. In the first cycle UH 1 daily value increased to 67.5 students who have increased as much as 10.65%, completeness students also increased to 12 students and 8 students have not been completed by 60% the percentage of completeness. In the second cycle increases in value as much as 14,81% to 77.5 with the expected goals to 19 students who completed and there are still 1 students who have not completed. Improved learning outcomes are supported with maximum learning process. Activities teachers in the first cycle-one meetings to gain success 70.83% with kriterian well. At the 2nd meeting increased to 79.17% with good criterion. In the second cycle-one meetings to acquire 87.5% success criteria. At the 2nd meeting increased to 95.83% with good criterion once. Activities students-one meeting to the first cycle of successes 58.33% with less criteria. At the 2nd meeting is 66.67% with sufficient criteria. In the second cycle to meeting all first gained success 75% with good criterion. At the 2nd meeting increased to 87.5% with good criterion. Thus, it can be concluded that the model type STAD cooperative learning can improve learning outcomes IPS class  IV SDN 011 Desa Talang Gedabu Kecamatan Rakit Kulim. Keywords: cooperative learning model STA, learning outcomes IPS